Pilot based Pre FFT channel estimation for OFDM systems in rayleigh-fading channel - Khan, A.M. (IEEE Computer Society, 2014)
Channel impairments degrade the performance of accurate data signal detection and decoding. The said problem becomes further severe in low SNR environment. As a result it reduces the performance of channel estimation. To alleviate this problem we develop a pilot based Pre FFT (time domain) channel estimation technique in the presence of Rayleigh fading channel. A novel time domain channel estimation technique is proposed that accurately measure the channel impulse response by using cross correlation between received signal and pilot carriers, especially at low SNR. In addition, the proposed technique enhances robustness in Orthogonal Frequency Division Multiplexing (OFDM) channel estimation by reducing Mean Square Error (MSE). Simulation results show that proposed method provides better accuracy in term of MSE over conventional techniques (LS and MMSE) that estimate the channel impulse response in frequency domain. Â© 2014 IEEE.